Physical Fitness Perception and Physical Education Enjoyment in 11- to 12-Year-Old Children - Francisco José Borrego-Balsalobre; Francisco Cavas-García; Arturo Díaz-Suárez; Alfonso Martínez-Moreno (MDPI AG, 2022)
Childhood motor competence plays a fundamental role in long-term adherence to physical activity. Enjoyment levels and self-perception of physical fitness increase motivation, commitment, and participation in physical activity. The objective of this study was to assess the body mass index (BMI), weight percentile, health status, physical fitness, and enjoyment levels of physical activity. A sample of 138 persons, of whom 67 were males and 71 females, with a mean BMI of 20.04 (2.35) answered the questionnaires Physical Activity Enjoyment Scale and the International Fitness Scale-self-report of physical fitness in young people. Tests were administered to measure functional fitness and anthropometric characteristics. Statistical analysis included calculation of Cronbach's alpha, ANOVA and Pearson's bivariate test correlations. The data indicate the reliability of the International Fitness Scale. No significant differences by gender were observed for the Physical Activity Enjoyment Scale. The BMI showed that significant positive correlations with 20 m sprint scores (p < 0.001, r = 0.367) and significant negative correlations with 6-minute lap scores (p < 0.001, r = −0.360) could be caused by an older physiological age. The overall physical fitness level of the children was medium-high, with most of the children enjoying physical education classes and slightly higher enjoyment values for males 40.88 (5.42) than females 40.31 (6.16).